Effective Strategies in Teaching Islamic Character Education in the Digital Era - Syarif, Aiman; Sahidin (Zona Education Indonesia, 2024)
This study explores effective strategies in teaching Islamic character education in the digital era using a qualitative approach. The methods applied include literature study, in-depth interviews, content analysis, and observation. Key findings suggest that the use of technology, such as Islamic-based learning apps and social media, significantly strengthens children's character values. Apps such as Quranic and Muslim Kids TV as well as educational content on social media platforms help convey Islamic teachings in an interactive and engaging way, increasing student motivation and engagement. Adaptive teaching methods, such as project-based learning and storytelling, have also p roven to be effective in instilling Islamic values. However, major challenges include digital content surveillance and limited tech skills among teachers and parents. This study emphasizes the importance of training and support for educators and parents to optimize the use of technology in Islamic character education. In conclusion, technology has great potential to support Islamic character education, with the right strategy and adequate supervision, to create a young generation with noble character and high integrity in the digital era